Cibinetide dampens innate immune cell functions thus ameliorating the course of experimental colitis. Issue 1 (December 2017) - Nairz, Manfred; Haschka, David; Dichtl, Stefanie; Sonnweber, Thomas; Schroll, Andrea; Aßhoff, Malte; Mindur, John; Moser, Patrizia; Wolf, Dominik; Swirski, Filip; Theurl, Igor; Cerami, Anthony; et al.
Abstract Two distinct forms of the erythropoietin receptor (EPOR) mediate the cellular responses to erythropoietin (EPO) in different tissues. EPOR homodimers signal to promote the maturation of erythroid progenitor cells. In other cell types, including immune cells, EPOR and the ß-common receptor (CD131) form heteromers (the innate repair receptor; IRR), and exert tissue protective effects. We used dextran sulphate sodium (DSS) to induce colitis in C57BL/6 N mice. Once colitis was established, mice were treated with solvent, EPO or the selective IRR agonist cibinetide. We found that both cibinetide and EPO ameliorated the clinical course of experimental colitis in mice, resulting in improved weight gain and survival. Correspondingly, DSS-exposed mice treated with cibinetide or EPO displayed preserved tissue integrity due to reduced infiltration of myeloid cells and diminished production of pro-inflammatory disease mediators including cytokines, chemokines and nitric oxide synthase-2. Experiments using LPS-activated primary macrophages revealed that the anti-inflammatory effects of cibinetide were dependent on CD131 and JAK2 functionality and were mediated via inhibition of NF-κB subunit p65 activity. Cibinetide activation of the IRR exerts potent anti-inflammatory effects, especially within the myeloid population, reduces disease activity and mortality in mice. Cibinetide thus holds promise as novel disease-modifying therapeutic of inflammatory bowel disease.